Distal and proximal hypoxia response elements cooperate to regulate organ-specific erythropoietin gene expression - Orlando, IMC; Lafleur, VN; Storti, F; Spielmann, P; Crowther, L; Santambrogio, S; Schödel, J; Hoogewijs, D; Mole, DR; Wenger, RH (Ferrata Storti Foundation, 2019)
While it is well-established that distal hypoxia response elements (HREs) regulate hypoxia-inducible factor (HIF) target genes such as erythropoietin (Epo), an interplay between multiple distal and proximal (promoter) HREs has not been described so far. Hepatic Epo expression is regulated by a HRE located downstream of the EPO gene, but this 3' HRE is dispensable for renal EPO gene expression. We previously identified a 5' HRE and could show that both HREs direct exogenous reporter gene expression. Here, we show that whereas in hepatic cells the 3' but not the 5' HRE is required, in neuronal cells both the 5' and 3' HREs contribute to endogenous Epo induction. Moreover, two novel putative HREs were identified in the EPO promoter. In hepatoma cells HIF interacted mainly with the distal 3' HRE, but in neuronal cells HIF most strongly bound the promoter, to a lesser extent the 3' HRE, and not at all the 5' HRE. Interestingly, mutation of either of the two distal HREs abrogated HIF binding to the 3' and promoter HREs. These results suggest that a canonical functional HRE can recruit multiple, not necessarily HIF, transcription factors to mediate HIF binding to different distant HREs in an organ-specific manner.